Electrochemically and Chemically Induced Redox Processes in Molecular Machines. Issue 4 (4th February 2015) - Le Poul, Nicolas; Colasson, Benoit
Abstract The controlled motion of ions, molecules, or supramolecular entities has inspired scientists for more than 25 years, and the concept remains of great interest for the development of moveable nanoscale objects for applications in electronics, medicine, and materials chemistry. Artificial molecular machines that involve electron exchange processes induced by electrical, chemical, or photochemical energy, have been widely developed. More specifically, machines that are stimulated by electrochemical means have been the focus of particular attention because such systems can allow the change of states to be followed and can enable access to mechanistic pathways through direct monitoring. Furthermore, these devices have the ability to connect the nanoscale machine to the macroscopic world, for instance by surface immobilization. In this review, we report recent examples of redox‐based molecular machines in both fluid solution and in organized or controllable environments such as modified electrodes, nanoparticles, polymers, gels, and liquid crystals. Basic concepts of molecular machinery and general applications are also discussed.